A Mendelian randomization analysis reveals the multifaceted role of the skin microbiota in liver cancer - Wang, Xiaoxue; Zhu, Zexin (Frontiers in Microbiology, 2024)
Background: Hepatocellular carcinoma (HCC, or Hepatic cancer, HC) and Cholangiocarcinoma (CCA, or Hepatic bile duct cancer, HBDC) are two major types of primary liver cancer (PLC). Previous studies have suggested microbiota can act as risk factors or preventive factors in PLC. However, no study reported the relationship between skin microbiota and PLC. Therefore, we employed a two-sample Mendelian randomization (MR) study to assess the causality between skin microbiota and PLC.The skin microbiota association genome-wide association study (GWAS) data were collected. The GWAS summary data for GCST90018803 (Hepatic bile duct cancer, HBDC) and GCST90018858 (Hepatic cancer, HC) were utilized in the discovery and verification phases, respectively. The inverse variance weighted (IVW) method was utilized as the principal method in our Mendelian randomization (MR) study. The MR-Egger intercept test, Cochran's Q test, MR-Pleiotropy RESidual Sum and Outlier (MR-PRESSO) and leave-oneout analysis were conducted to identify the heterogeneity and pleiotropy.The results showed that Veillonella (unc.) plays a protective role in HBDC, family: neisseriaceae has a positive association with HBDC risk. Class: betaproteobacteria, phylum: bacillota (firmicutes) and Veillonella (unc.) play a protective role in HC, S. epidermidis, Corynebacterium (unc.), family: neisseriaceae, Pasteurellaceae sp. were associated with an increased risk in HC.This study provided new evidence of the association between skin microbiota and PLC, suggesting that skin microbiota plays a role in PLC progression. Skin microbiota could be a novel and effective way for PLC diagnosis and treatment.